Influence of stockpile design on carbonation of waste concrete Implications for carbon management in China - Wang, Panxiu (Waste management & research : the journal of the International Solid Wastes and Public Cleansing Association, ISWA, 2024)
Enhancing the sequestration capacity of waste concrete is crucial for achieving carbon neutrality within the construction industry. Although existing studies primarily focus on theoretical analysis of concrete carbon sequestration, limited attention has been paid to explore the potential of waste concrete sequestration during stockpiling phase under varying environmental conditions. To fill this knowledge gap, we developed a CO2 uptake calculation model tailored for the stockpiling phase of waste concrete. This model investigates the impact of crush size, stacking method and environmental conditions on the total carbon sequestration capacity and efficiency, identifying the most advantageous approach. Our findings reveal the following: (1) Increasing the crush size of waste concrete enhances its carbon sequestration capacity, albeit extends the sequestration duration. A crush size of 5-20 mm is deemed optimal for achieving the desired sequestration efficiency. (2) The optimal stacking method involves smaller piles with reduced radii and angles. (3) High temperatures and humidity levels accelerate the sequestration rate. Practical measures such as watering and covering can be employed to enhance carbon sequestration. (4) In 2021, China's waste concrete exhibited a declining sequestration potential from the southeast to the northwest and northeast regions. The maximum sequestration potential has the capacity to neutralize up to 4% of the carbon emissions generated by the construction industry in that year. This research provides a foundation for accurate assessment and the development of effective carbon sequestration strategies for waste concrete